2020
DOI: 10.38157/entrepreneurship-review.v1i2.166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strategic Intent on Performance of Small and Medium Scale Printing Press Firms in Abuja, Nigeria

Abstract: Purpose: This study investigates the effect of strategic intent on the performance of small and medium scale printing firms in Federal Capital Territory (FCT), Abuja, Nigeria. Methods: The population of the study included all the small and medium scale printing press in Abuja which is 226 and the sample size of 68. A multiple regression model was formulated to estimate the effect of strategic intent (vision, mission, and objectives) on performance (growth) of small and medium scale printing press firms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Although the study (Worthington and Patton, 2005) demonstrated the value of SI in establishing green management in small and medium-sized businesses with two aspects (deduction and response). A study (Owens and Khazanchi, 2021) took (SI) dimensions from the perspective of implementation, initiative and foresight and fully agrees with the study (Mburu and Thou, 2015) focusing on the dimensions that were identified according to the model (Hamel and Prahalad, 1989) as well as a study (Glaa, 2021) (Lassas, 2021) (Obonyo, 2020) (Eze et al , 2020) (Gabow and Kinyua, 2018), which focused on the same dimensions adopted in our current study and applied in different environments. The studies (Odita and Bello, 2015) and (Oriesek and Schwarz, 2021) rely on the fact that (SI) is linked to the future and as a result it is linked to the organization's mission, future vision, and expected outcomes.…”
Section: Theoretical Background and Hypotheses Formulationsupporting
confidence: 59%
“…Although the study (Worthington and Patton, 2005) demonstrated the value of SI in establishing green management in small and medium-sized businesses with two aspects (deduction and response). A study (Owens and Khazanchi, 2021) took (SI) dimensions from the perspective of implementation, initiative and foresight and fully agrees with the study (Mburu and Thou, 2015) focusing on the dimensions that were identified according to the model (Hamel and Prahalad, 1989) as well as a study (Glaa, 2021) (Lassas, 2021) (Obonyo, 2020) (Eze et al , 2020) (Gabow and Kinyua, 2018), which focused on the same dimensions adopted in our current study and applied in different environments. The studies (Odita and Bello, 2015) and (Oriesek and Schwarz, 2021) rely on the fact that (SI) is linked to the future and as a result it is linked to the organization's mission, future vision, and expected outcomes.…”
Section: Theoretical Background and Hypotheses Formulationsupporting
confidence: 59%
“…The fourth determinant is firm strategy, structure, and rivalry, which refer how a company is established, organized, and managed (Mross, 2005), (Jeong et al, 2017) (Eze et al, 2020). In the Malaysian printing industry, competitiveness is affected by the industry's competitiveness.…”
Section: The Competitive Advantage Of Nations (Can) Modelmentioning
confidence: 99%
“…This is so because an organisation should possess certain capabilities that others do not have or cannot easily and promptly imitate. An organisation's mission is a measurable target or benchmark that must be met to attain the goal (Eze et al, 2020). Sande and Nyadzo (2022) stated that organisational Missions kindle the enthusiasm and spirits of employees at all levels.…”
Section: Mission and Organisational Performancementioning
confidence: 99%